intro to chain rule
The chain rule in calculus is finding the derivative for two or more products of themselves. For example F(x)= (x+3)^4 where F(x)= G(H(x)) and G(x)= (x)^4, H(x)= x+3. Then you would use the chain rule to find the derivative. This rule is simple, yet it can be hard to differentiate the different individual functions. So fo this example the derivative F'(x)=G'(H(x))*H'(x). One easy way to remember is to think, derivative of the outside times derivative of the inside. Lets dive into it…..
lets label the functions G(x) and H(x) where F(x)=G(H(x)) and G(x)= x^4 , H(x)= x+3
G'(x)= 4x^3 and H'(x)= 1
F'(x)= 4(H(x))^3 * H'(x)
F'(x)= 4(x+3)^3 * 1
About The Author
|I have never been a tutor but I have had friends who were tutors. I have exceptional math and science knowledge. I have taken math up to Calculus II and have taken numerous science courses including but not limited to, astronomy, biology, marine biology, ecology, geology, chemistry, aqueous chemistr...|